A randomised group comparison controlled trial of 'preschoolers with autism': A parent education and skills training intervention for young children with autistic disorder. (February 2014) - Tonge, Bruce; Brereton, Avril; Kiomall, Melissa; Mackinnon, Andrew; Rinehart, Nicole J
Aim: To determine the effect of parent education on adaptive behaviour, autism symptoms and cognitive/language skills of young children with autistic disorder. Method: A randomised group comparison design involving a parent education and counselling intervention and a parent education and behaviour management intervention to control for parent skills training and a control sample. Two rural and two metropolitan regions were randomly allocated to intervention groups ( n = 70) or control ( n = 35). Parents from autism assessment services in the intervention regions were randomly allocated to parent education and behaviour management ( n = 35) or parent education and counselling ( n = 35). Results: Parent education and behaviour management resulted in significant improvement in adaptive behaviour and autism symptoms at 6 months follow-up for children with greater delays in adaptive behaviour. Parent education and behaviour management was superior to parent education and counselling. We conclude that a 20-week parent education programme including skills training for parents of young children with autistic disorder provides significant improvements in child adaptive behaviour and symptoms of autism for low-functioning children.